Comparative Analysis of Complicated Urinary Tract Infections Caused by Extensively Drug-Resistant Pseudomonas aeruginosa and Extended-Spectrum β-Lactamase-Producing Klebsiella pneumoniae - Elena Sendra; Inmaculada López Montesinos; Alicia Rodriguez-Alarcón; Juan Du; Ana Siverio-Parés; Mar Arenas-Miras; Esperanza Cañas-Ruano; Nuria Prim; Xavier Durán-Jordà; Fabiola Blasco-Hernando; Enric García-Alzorriz; Francesc Cots; et al. (MDPI AG, 2022)
The objective was to compare clinical characteristics, outcomes, and economic differences in complicated urinary tract infections (cUTI) caused by extensively drug-resistant Pseudomonas aeruginosa (XDR P. aeruginosa) and extended-spectrum beta-lactamase-producing Klebsiella pneumoniae (ESBL-K. pneumoniae). A retrospective study was conducted at a tertiary care hospital. Patients with XDR P. aeruginosa and ESBL-K. pneumoniae cUTIs were compared. The primary outcome was clinical failure at day 7 and at the end of treatment (EOT). Secondary outcomes: 30- and 90-day mortality, microbiological eradication, and economic cost. Two-hundred and one episodes were included, of which 24.8% were bloodstream infections. Patients with XDR P. aeruginosa cUTI more frequently received inappropriate empirical therapy (p < 0.001). Nephrotoxicity due to antibiotics was only observed in the XDR P. aeruginosa group (26.7%). ESBL-K. pneumoniae cUTI was associated with worse eradication rates, higher recurrence, and higher infection-related readmission. In multivariate analysis, XDR P. aeruginosa was independently associated with clinical failure on day 7 of treatment (OR 4.34, 95% CI 1.71-11.04) but not at EOT, or with mortality. Regarding hospital resource consumption, no significant differences were observed between groups. XDR P. aeruginosa cUTI was associated with worse early clinical cures and more antibiotic side effects than ESBL-K. pneumoniae infections. However, no differences in mortality or in hospitalization costs were observed.